Morphology and chaetotaxy of the larval stages of Andogyrus seriatopunctatus Régimbart (Coleoptera: Adephaga: Gyrinidae) - Archangelsky, Miguel; Michat, Mariano C. (Zootaxa, 2007)
The larval stages of Andogyrus seriatopunctatus Régimbart are described and illustrated, including morphometric and chaetotaxic characters. A larval ground pattern for the chaetotaxic characters is presented; it is based on first instar larvae of A. seriatopunctatus. Unidentified larvae of Dineutus MacLeay and a third instar larva of Gyrinus argentinus Steinheil were also inspected. For chaetotaxic homologization comparisons with other adephagan families were performed, mainly with Carabidae and Dytiscidae. The ground pattern is considered provisional due to the lack of previous studies in this family. Larvae of A. seriatopunctatus are briefly compared to those of A. buqueti (Aubé). Notes on the biology of A. seriatopunctatus are also included.